SEJARAH PERKEMBANGAN AL-QUR’AN SEBAGAI MATERI PENDIDIKAN AGAMA ISLAM DI INDONESIA - Hamid, Abdul; Agil Tamam (BAMALA Institute, 2024)
The history of the development of the Qur'an as a material for Islamic religious education in Indonesia has experienced a long and varied journey, along with the entry of Islam in the archipelago in the 13th century to the modern era today. This study aims to examine the history of the development of the Qur'an as a material for Islamic religious education in Indonesia, as well as to evaluate the learning methods applied from time to time. The method we use in this study is a qualitative approach with historical methods and literature analysis to collect data related to changes and innovations in learning the Qur'an. The results of the study show that in the early days of Islam in Indonesia, the Qur'an was taught informally, although only through the halaqoh system in mosques and prayer rooms. During the colonial period, there was a transformation with the implementation of a more formal and structured Qur'anic education system as a response to colonial influence. After independence, the Qur'anic learning method underwent modernization, with the increasing use of new technologies and methods such as sorogan qiro'ati, the ummi method, and iqra' which were designed to improve the efficiency and understanding of students. In conclusion, the history of the development of the Qur'an as a material for Islamic religious education in Indonesia shows how developed Qur'anic education has been from the beginning of Islam's entry into Indonesia until the modern era today and also the enthusiasm to study and practice the teachings of the Qur'an remains high in Indonesia, even though this education faces various challenges and obstacles